Vpliv nasilja v vizualnih medijih na vedenje mladih - Mrevlje, Urša Petja (Medicinski razgledi, 1997)
Volence is becoming icreasingly present in modern society. Its consequences are manifested in a large number of injuries and premature deaths and thus violence is becoming a great problem for public health. My decision to undertake this research was spurred by thefact that violent behaviour among adolescents is increasingly present in Slovenia and because of the influence of the visual media on human perceptions of the real wodl. Considering the increasing significance that the media have on the life of modern man and on the psycho-social development of children and adolescents, lendeavoured to evaluate the influence of violence in the media on violent behaviour of adolescents. The research group was comprised of 62 adolescents of both genders in the age group from 15 to 19 years who are inmates of adolescent rehabilitation centres. The control group comprised 87 gender and age compatible high school students. A questionare was given to both of these groups that evaluates family conditions, violence in the family, attitudes towards violence, vilent behaviour, autoaggressivness and behaviour related tothe media. In order to evaluate aggressive behaviour as individualised characteristics we used the standardised Buss-Durkee questionnaire. Adolescents from the research group differed from the control group inthe experience with violence in the family, in their personal violent behaviour, in attitude toward violence, in autoaggressivness and in their response, experience and motivationfor accepting violence in the media. These differences were statistically significant. (Abstract truncated at 2000 characters.)
Keywords: nasilje; mladostniki; aggressiveness; agresivnost; množični mediji; mass media; družina; family